Promoting access to healthcare for trans and gender diverse persons in Zimbabwe in the context of HIV - Ngwena, Charles (University of Pretoria, 2025)
Mini Dissertation (MPhil (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.